Delírios conservadores+fundamentalistas:cisnormatividade, linguagem e educação - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Language is a field that is immeasurable. There are so many things articulated when we stop to feel this thing that is language that if we blink, something passes by, but just as quickly something else appears. I think this academic work is a bit about that. I looked at my life, and this piece is an extension of me. It is how I feel the world, I read the world, the lens through which I view it. Whoever reads this will be entering my body+mind+spirit and feeling how I perceive, in this moment, discussions about language, school, linguistic education, disobedience and gender disobedience. In addition, you will also feel how I analyze and how I read conservative+fundamentalist fields using these institutions. I know that most of these groups know very well that the school actively reproduces racial, ethnic, gender, sexual orientation and class based violence, in other words, the countless violence of modernity+coloniality+capitalist+cisheteropatriarchal violence. These pages also try to discuss that, but much beyond that, I talk about our disobedient power, which in fact is way beyond our resistant potency. This work goes through all these arguments, looking at bills (PL117/2021 and PL120/2021) presented to the Ponta Grossa City Council, trying to show how the supposed attempts in "defense the family and children" go beyond conservatives+fundamentalists domains seeking to maintain their access and privileges, looking more directly at the productions of cisnormativity and cissupremacy, but necessarily articulated with white supremacy, richness and heteronormativity. But, beyond that, this text is also an agglomeration of productions that, despite all these disgraces, create other possibilities for the world.

El lenguaje es un campo inconmensurable. Hay tantas cosas articuladas cuando nos detenemos a sentirlo que si parpadeamos algo pasa, pero con la misma rapidez aparece algo más. Creo que todo este trabajo tiene que ver un poco con eso. Miré mi vida y este trabajo es una extensión de mí. Así es como siento el mundo, leo el mundo, a través de qué lentes. Quien lea, estará entrando en mi cuerpa+mente+espírita y sintiendo cómo percibo, en ese momento, las discusiones sobre el lenguaje, la escuela, la educación lingüística, la desobediencia, la desobediencia de género. Además, también sentirá cómo leo los campos conservadores+fundamentalistas usando estas instituciones. Sé que la mayoría de estos grupos saben muy bien que la escuela reproduce activamente la violencia racial, étnica, de género, de sexualidad, de clase, en fin, las incontables violencias de la modernidad+colonialidad+capitalista+cisheteropatriarcal. Estas páginas también tratan de decir sobre eso, pero mucho más allá de eso, digo sobre nuestra potencia desobediente, que de hecho está mucho más allá de nuestra potencia resistente. Este trabajo pasa por todas estas discusiones, mirando los proyectos de ley (PL117 / 2021 y PL120 / 2021) presentados a la Sala de Ponta Grossa, tratando de mostrar cómo los supuestos intentos de "defensa de la familia y de las niñas" no son más que registros en los campos conservadores+fundamentalistas para mantener sus accesos y privilegios, mirando más directamente a las producciones de la cisnormatividad y la cissupremacía, pero necesariamente articuladas a la supremacía blanca, la riqueza y la heteronormatividad. Pero, más allá de eso, esta producción es también una aglomeración de producciones que, a pesar de todas estas desgracias, crean otras posibilidades para el mundo.
Keywords: linguagem; transgeneridade; cisgeneridade; transfeminismos; educação linguística; desobediência; language; transgender; cisgender; transfeminisms; linguistic education; disobedience; CNPQ::LINGUISTICA, LETRAS E ARTES